Pengaruh Indeks Harga Saham Regional ASEAN dan Variabel Makroekonomi terhadap Indeks Harga Saham Syariah Indonesia (ISSI) - Aurora Nur Firdausi; Idqan Fahmi; Imam T Saptono (Department of Islamic Economics, IPB University, 2016)
Investment in Indonesia is currently undergoing a good development. It is characterized by the good performance of the composite stock price index (IHSG), LQ45, Jakarta Islamic Index (JII), and Indonesia Sharia Stock Index (ISSI), which represents the actual conditions of the national Sharia capital market. The market share of the stock of Sharia has reached 58,89% of all issuers of stocks with the highest market capitalization of Rp 2,946 trillion, or of 56,37% of total market capitalization. The presence of Islamic capital market is expected to boost the performance of the national economy. Entering the ASEAN economic community 2015, the economy of Indonesia need more stable to be able to compete with the global economy. Stability macroeconomic factors of a country as well as the absorption of investment from domestic and foreign investors will be important in the face of ASEAN economic community. This research attempts to examine the impact of ASEAN stock market and macroeconomic variables towards Indonesia Sharia Stock Index (ISSI). By using Vector Error Correction Model (VECM) as the method, this research utilizes time series monthly data from May 2011 to June 2015.